Initial experience of a large, self‐expanding, and fully recapturable transcatheter aortic valve: The UK & Ireland Implanters' registry. Issue 4 (5th November 2018) - Dowling, Cameron; Firoozi, Sami; Doyle, Niamh; Blackman, Daniel J.; Malkin, Christopher J.; Cunnington, Michael S.; Saraf, Smriti; Buch, Mamta H.; Levy, Richard; Chowdhary, Saqib; Spence, Mark S.; Manoharan, Ganesh; et al.
Abstract: Objectives : The UK & Ireland Implanters' registry is a multicenter registry which reports on real‐world experience with novel transcatheter heart valves. Background : The 34 mm Evolut R transcatheter aortic valve is a self‐expanding and fully recapturable transcatheter aortic valve, designed to treat patients with a large aortic annulus. Methods : Between January 2017 and April 2018, clinical, procedural and 30‐day outcome data were prospectively collected from all patients receiving the 34 mm Evolut R valve across 17 participating centers in the United Kingdom and Ireland. The primary efficacy outcome was the Valve Academic Research Consortium‐2(VARC‐2)‐defined endpoint of device success. The primary safety outcome was the VARC‐2‐defined composite endpoint of early safety at 30 days. Results : A total of 217 patients underwent attempted implant. Mean age was 79.5 ± 8.8 years and Society of Thoracic Surgeons Predicted Risk of Mortality Score 5.2% ± 3.4%. Iliofemoral access was used in 91.2% of patients. Device success was 79.7%. Mean gradient was 7.0 ± 4.6 mmHg and effective orifice area 2.0 ± 0.6 cm 2 . Paravalvular regurgitation was more than mild in 7.2%. A new permanent pacemaker was implanted in 15.7%. Early safety was demonstrated in 91.2%. At 30 days, all‐cause mortality was 3.2%, stroke 3.7%, and major vascular complication 2.3%. Conclusions : Real‐world experience of the 34 mm Evolut R transcatheter aortic valve demonstrated acceptable procedural success, safety, valve function, and incidence of new permanent pacemaker implantation.